Ecolinguistic study of the writing works of achieving students Bali State Polytechnic in 2020 - Paulus Subiyanto; I Ketut Sadia; IGA Paramita Dewi (English, 2020)
Bali State Polytechnic (PNB) has used the label "green", such as the "green campus" and "green tourism", as a flagship program to show its concern for ecological awareness. Ecolinguistics is a combination of linguistics and ecology studying the relationship between the use of language in discourse related to the environment. This study aims to see how the ecological insights possessed by outstanding students are revealed through their written works (languages). From the primary data source in the form of 10 written works of achieving students in 2020, ecological insights will be identified in which they are revealed in the choice of words containing ecological content. The results show that the average ratio of ecological word used and the number of words in writing is 0.84%, while the average vocabulary, 9 types of ecological words for each writing contain an average of 2065 words. With the assumption based on the cognitive linguistic theory that thoughts are expressed through language, it can be concluded that students' ecological insight and awareness have not developed optimally as far as it is expressed through word choice (diction). It suggests that the PNB students need to broaden their ecological insights through language learning, especially reading texts based on ecolinguistics.